CARBON STOCK EVALUATION AND ITS POTENTIAL CARBON MARKET VALUE IN CAREY ISLAND MANGROVE FOREST, SELANGOR, MALAYSIA - H A, Ashokri; M Z, Rozainah (MATTER: International Journal of Science and Technology, 2015)
This study was carried out to examine the total carbon stock and its potential carbon market value at Carey Island mangrove forest, Selangor, Malaysia. Two sites were chosen: ODCC "by the sea" and Kg. Melayu "riverine" as they represent the dominant mangrove tree species, (Avicennia Alba, Rhizophora apiculata, Rhizophora mucronata and Xylocarpus granatum). Data collection was done across three seasons: Intermediate, dry and wet for both sites in order to get one year average. Sampled mangrove species were sorted out into leaves, stems, bark (aboveground), roots (belowground) and litter; sediment samples were collected at 0-10, 10-20 and 20-30 cm deep. Carbon organic content was determined using furnace (LOI) followed by a conversion factor of (1.724). Data obtained were utilized to compare the results between species, tree partitioning, soil depth, seasons and different settings. Results showed that carbon was more allocated in the dry season within the bark and 20-30 cm deep underground. In vegetations, results have revealed that carbon allocation was very similar (bark > stem > leaf >root) even though both sites represent different species. Litter carbon allocation was in the order of: propagules > leaf > branch in ODCC and branch > propagules > leaf in Kg.Melayu. In sediment, results brought to light that carbon allocation increases with soil depth. The total carbon stock was estimated at 648.73 (t/ha/yr) in ODCC and (600.18) t/ha/yr in Kg.Melayu with soil carbon stock representing 98% and 99% of the total carbon stock in ODCC and Kg. Melayu respectively. The total coverage of mangrove forest is Carey Island was estimated 182.72 ha using Arc GIS 10.1. The potential carbon market value for Carey Island was in a range of USD 0.6 – 21.8 million.